Intensification pathways and sustainability of crop-livestock systems in Sub-Saharan Africa: crop-livestock interaction contribution - (:unkn) unknown (My University, 2017)
In sub-Saharan Africa savannas, mixed crop-livestock systems are dominant and crop-livestock association keeps on growing. Does it contribute to intensify agricultural production and farms sustainability? To answer this question, the study compares according to the level of association between agriculture and livestock: the characteristics, trajectories, intensifying profiles and sustainability indicators of farms inWestern Burkina Faso and Northern Cameroon, divided into three groups (farmers, agro-pastoralists and breeders). The level of association between agriculture and livestock was estimated by the amount of carbon retained annually on the farm in the form of organic manure, crop residues used as fodder and livestock feed. Farms with a high level of association between agriculture and livestock (high carbon retention rates) are larger and have better overall indicators of sustainability. Farm trajectories and intensification pathways have been highlighted: they are not specific of the levels of association between agriculture andlivestock, but they are specific of the three farmgroups (farmers, agro-pastoralists and breeders).
Keywords: African Research